1984
DOI: 10.1002/pol.1984.170221021
|View full text |Cite
|
Sign up to set email alerts
|

Determination of carbonyl‐containing functional groups in oxidized polyethylene

Abstract: SynopsisA combined (chemical and infrared (IR) spectrophotometric) method is discussed for the simultaneous determination of concentrations of carboxyl (A), ketone (K), and ester (E) groups formed in the oxidation of polyethylene (PE). The IR absorptivities of these functional groups were determined by using model compounds [stearic acid, stearone, poly-(1,4-butylene sebacate)]. The integral absorption of the C=O band of polymer samples which contained several 0x0 groups of different types was found to be addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…Generally, AB‐type diblock copolymers such as PIB‐ block ‐PS and PS‐ block ‐PIB (where PS is polystyrene and PIB is polyisobutylene) have been prepared by sequential cationic polymerization including three‐step1 or two‐step2–5 synthesis with end‐functionalized PS or PIB in conjunction with an alkylaluminum, such as diethylaluminum chloride (Et 2 AlCl);1–5 the final copolymers have been obtained by selective solvent extraction. Diblock copolymers and glassy–rubbery–glassy ABA‐type linear or three‐arm star triblock copolymers, where A is PS or poly(α‐methylstyrene) and B is PIB, have also been prepared by the one‐pot sequential monomer addition to living cationic polymer charges 6–16. These procedures use a monofunctional, difunctional, or trifunctional initiator in conjunction with TiCl 4 6–14.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, AB‐type diblock copolymers such as PIB‐ block ‐PS and PS‐ block ‐PIB (where PS is polystyrene and PIB is polyisobutylene) have been prepared by sequential cationic polymerization including three‐step1 or two‐step2–5 synthesis with end‐functionalized PS or PIB in conjunction with an alkylaluminum, such as diethylaluminum chloride (Et 2 AlCl);1–5 the final copolymers have been obtained by selective solvent extraction. Diblock copolymers and glassy–rubbery–glassy ABA‐type linear or three‐arm star triblock copolymers, where A is PS or poly(α‐methylstyrene) and B is PIB, have also been prepared by the one‐pot sequential monomer addition to living cationic polymer charges 6–16. These procedures use a monofunctional, difunctional, or trifunctional initiator in conjunction with TiCl 4 6–14.…”
Section: Introductionmentioning
confidence: 99%
“…Diblock copolymers and glassy–rubbery–glassy ABA‐type linear or three‐arm star triblock copolymers, where A is PS or poly(α‐methylstyrene) and B is PIB, have also been prepared by the one‐pot sequential monomer addition to living cationic polymer charges 6–16. These procedures use a monofunctional, difunctional, or trifunctional initiator in conjunction with TiCl 4 6–14. A mixture of BCl 3 –TiCl 4 coinitiators has been used for the one‐pot synthesis of block star copolymers consisting of PIB‐ b ‐PS arms 15, 16.…”
Section: Introductionmentioning
confidence: 99%
“…6 Benzoyl peroxide mediated functionalization of LLDPE by tetra hydro phthalic anhydride and maleic anhydride had reported by Campos et al 7 The carbonyl functionalization by c-radiation dosimetry of LDPE was reported. 8 Fodor et al 9 determined the carbonyl containing functional groups in the oxidized polyethylene. N-Vinyl pyrrolidone was grafted onto LDPE by c-radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The UV spectrum in the 200-350 nm range of PE with the antioxidant compound is shown in Fig. 1 assigned to phenyl groups, which are present in most antioxidant systems (2). We have observed that press-molding above 120°C leads to loss of some antioxidant (i.e.…”
Section: Uv Measurementsmentioning
confidence: 92%